THE PHENOMENON OF SOCIAL DISCRIMINATION NOWADAYS AND THE LEGAL SYSTEMS OF EXTINGUISHMENT - Aspasia-Maria, Vasilaki (European Scientific Journal, ESJ, 2015)
Despite the fact that during the last years, the international and european community has made some important progress in the fight against racism, racial and religious discrimination, xenophobia and related intolerance through the implementation of national and international law systems and the foundation of numerous international human rights mechanisms and organizations, the economical, political and technological progress nowadays encourages the maintenance of the phenomenon of social discrimination and the danger of its future expansion. To fight this issue, the international community needs the improvement of its legal systems through a deep consideration of the problem and the development of innovative and cooperative solutions.